Reformacija in Šaleška dolina - Ravnikar, Tone (Stati inu obstati, 2009)
The paper presents those responsible for Lutheran ideas and the organizational forms of Protestantism in the Šaleška dolina valley. This territory belonged to the Ljubljana diocese and such examples of the morally unacceptable life and activity of the Roman Catholic priesthood as were noticeable in other parishes were frequent here too. As early as 1528 the Roman Catholic commission established that the owners of castles (Velenje, Forhtenek, Švarcenštajn) and the judge of the market town of Šoštanj were opposing masses and forbidding their subjects to attend mass. The Velenje lord of the castle, Baltasar Wagen, drove out the Roman Catholic priest from the Velenje church of the Mother of God and brought in a Lutheran preacher, which triggered a longlasting dispute over this church between Wager and the Roman Catholic church authorities. In Šoštanj and Velenje there were adherents of Lutheranism among the townspeople as well. In Velenje a German preacher worked from 1573 and from 1576 Jurij Cvetić, who had a command of Slovene. Also in Velenje the Protestants opened the first elementary school in Šaleška dolina in 1574 (it functioned until c. 1600). Noblemen from Šaleška dolina gave financial support to build a house of prayer in Golče near Žalec, which was the only newly built Protestant church building in Slovenia. The preacher Ivan Dolijanski worked here. At Švarcenštajn Castle a stock of Slovene and German Bibles was kept, which were distributed around Styria. Nevertheless the Reformation endeavours in Šaleška dolina remained tied to the nobility and a few individuals in the market towns of Šoštanj and Velenje, while religious conflicts often involved interests regarding estatesand incomes.
Keywords: protestantizem; reformacija; Šaleška dolina; zgodovina